Detritos foliares em riachos subtropicais: dinâmica de matéria orgânica, processo de decomposição e macrofauna associada - König, Rodrigo (2013)
Low-order forested streams are dependent on allochthonous material input and the main energy source is obtained from leaf litter provided by the surrounding vegetation. Several gaps need to be filled to the knowledge of this process in subtropical environments and, accordingly, the thesis aimed to conduct some investigations considering the decomposition of leaf litter in streams. Four studies were conducted in subtropical streams with the following objectives: a) to verify the quantitative importance of the leaf input into streams, the main sources of input and its variation over the year; b) to analyze the influence of the leaf litter quality on decomposition and macroinvertebrate colonization; c) to evaluate the influence of the land use on the decomposition process, including the macroinvertebrate community and fungi; d) to conduct an initial investigation about the influence of insecticide application on the macroinvertebrate community that colonizes leaves in streams. Leaf litter was the main plant component to come in stream and the main route of entry allochthonous material was vertical. We observed the influence of season on this entry, with an increase mainly in the autumn and in the months with high rainfall. The chemical characteristic of leaves influenced the decomposition of leaf litter and its colonization by the macroinvertebrate community. Leaves with higher nitrogen content and lower amount of components that hinder decomposition were processed more quickly and, for these reasons, showed a higher amount of shredders. Moreover, different land uses did not significantly influence the decomposition process, just modifying some aspects of the macroinvertebrate community, especially in streams with urban influence. The results may be due to high currents found in local streams that make homogeneous its consequences for water quality, for the biological component and hence for ecological processes such as decomposition. We observed an influence of insecticide application on the macroinvertebrate community, decreasing the abundance of the target groups of the product, but generating an increase in the richness and abundance of other groups after an initial period of colonization.